Pengembangan Media Pembelajaran Berbasis Web Pada Mata Pelajaran Fisika Materi Hokum Newton Kelas X Di Sma Negeri 2 Ende - Fransiska Helmina Ndari; Maria Adelvin Londa; L. B. Finansius Mando (Teknik Komputer Politeknik Negeri Sriwijaya, 2023)
Abstract The problem in this study is that students only see, read, and hear, unable to interact with learning media directly. When the Covid pandemic hit the world ofteaching and learning activities stopped completely because the Negri 2 Ende High School had not implemented online-based learning media or websites. The purpose of this study is to find out the development of website-based learning media on Newton's Law class X material at SMA Negri 2 Ende. The researchmethod used in this study is research and development (R&D). data collectiontechniques in the form of observation, documentation and interviews. the development method uses the ADDIE model and the testing uses black box testing. The results showed that the learning process of students before and after using learning media has improved very well.this learning media has received a positive response from the SMA Negeri 2 Ende institution, teachers and also class X students. The conclusion is that it can implement the development of web-based learning media in the subject of newton legal material physics class x SMA Negeri 2 Ende. Keywords— research and development (R&D) method, ADDIE model, Black box testing